4DMRI-based analysis of inter— and intrafractional pancreas motion and deformation with different immobilization devices. (10th January 2019) - Dolde, Kai; Dávid, Christian; Echner, Gernot; Floca, Ralf; Hentschke, Clemens; Maier, Florian; Niebuhr, Nina; Ohmstedt, Kai; Saito, Nami; Alimusaj, Merkur; Fluegel, Beate; Naumann, Patrick; et al.
Abstract: Time-resolved magnetic resonance imaging (4DMRI) provides spatial motion information with high soft-tissue contrast. This study exploits the potential of 4DMRI by investigation of inter- and intrafractional pancreas motion and deformation with different patient immobilization devices. In total, 150 4DMRI scans were acquired for a cohort of 5 volunteers, each was scanned in 10 imaging sessions using three different positioning modes (flat table top (FTT), vacuum bag (VB), abdominal corset (AC)), respectively, to simulate repeated 4DMR imaging sessions of patients during fractionated radiotherapy. Large pancreatic motion variations were observed throughout the volunteers with mean inferior-superior (IS) motion amplitudes up to 28.5/21.9 mm for FTT/VB measurements, which were reduced by 48%/34%, respectively, by using abdominal corsets. Small IS motion reductions were present for vacuum bag measurements, compared to flat table top measurements. Corset measurements additionally showed an improved motion reproducibility between different days by more than 60% compared to FTT and VB. In anterior-posterior direction, motion amplitudes were reduced by 69%/60% for corset measurement, compared to FTT/VB, and their day-to-day fluctuations were reduced by approximately 130%. With respect to respiration-induced pancreas deformations, the pancreas showed the lowest deformation and highest reproducibility for corset measurements in 4 out of 5 volunteers. Moreover, both, the VB and AC setup showed a generally improved setup reproducibility compared to the non-immobilized flat table top setting. All in all, in this study, abdominal corsets showed to reduce both pancreatic motion and deformations. Moreover, by using corsets it is possible to improve the reproducibility of both pancreatic motion and deformation, which are important factors in radiotherapy treatments. Therefore, radiotherapy treatments of pancreatic cancer patients with abdominal corsets may be a viable option for patients with large internal organ motion amplitudes and may lead to a better consistency of the treatment planning and delivery situation.